LINC01133 and LINC01243 are positively correlated with endometrial carcinoma pathogenesis - Yang, Weina; Yue, Yingying; Yin, Fei; Qi, Zhiying; Guo, Ruimeng; Xu, Yanying (Archives of gynecology and obstetrics, 2021)
Purpose To characterize the role of two long non-coding RNAs (lncRNAs), LINC01133 and LINC01243, in endometrial carcinoma (EC) pathogenesis. LINC01133 is an lncRNA that has been implicated in many cancers, and LINC01243 is a newly identified lncRNA identified from the NCBI GEO database. Methods We studied the effect of LINC01133 and LINC01243 on EC malignancy using siRNA knockdown and real-time quantitative polymerase chain reaction (RT-qPCR), flow cytometry, Annexin V-FITC/propidium iodide double staining, Transwell, and scratch invasion assays in two EC cell lines (Ishikawa and HEC-1-A cells). Results We first confirmed the partial knockdown of both LINC01133 and LINC01243 expression in Ishikawa and HEC-1-A cells using RT-qPCR. Following confirmation of lncRNA knockdown, we assessed the effect of knockdown on EC malignancy. We observed reduced EC cell proliferation using the CCK-8 assay, as well as cell cycle arrest and increased apoptosis in both EC cell lines. Furthermore, Transwell and scratch invasion assays revealed decreased migration and invasion of the two EC cell lines, respectively. Conclusion We demonstrated that LINC01133 and LINC01243 expression are associated with EC development and progression. Our findings suggest a potential role for these lncRNAs as novel EC biomarkers.